A new approach to left sleeve pneumonectomy: complete VATS left pneumonectomy followed by right thoracotomy for carinal resection and reconstruction - Toshio Fujino; Masayuki Tanahashi; Haruhiro Yukiue; Eriko Suzuki; Naoko Yoshii; Masayuki Shitara; Yasunori Kaminuma; Hiroshi Niwa (Surgical Case Reports, 2018)
Abstract Background Left sleeve pneumonectomy is a challenging operation that requires individualized approaches. Here, we present a new minimally invasive combined thoracoscopic approach. Case presentation A 61-year-old woman was diagnosed with tracheobronchial adenoid cystic carcinoma. The tumor originated from the left main stem bronchus, and tumor with carinal involvement was observed. We judged that complete resection would be possible via left sleeve pneumonectomy. However, because tumor involvement with the esophagus and descending aorta was suspected, evaluation of resectability in advance was necessary. After confirmation via examination thoracoscopy of no involvement with the surrounding organs, complete VATS left pneumonectomy was performed and followed by right thoracotomy for carinal resection and reconstruction. Conclusions When thoracoscopic surgery becomes mainstream, this minimally invasive combined thoracoscopic approach might be an optimal option for patients who require left sleeve pneumonectomy.